Project Management Design Of UPS Installation On Cooper Type CCR Loads - Muhammad Caesar Akbar; Jhon Fernando Sijabat (Jurnal Ilmu Sosial Mamangan, 2024)
Air transportation is effective, efficient, fast, safe, and comfortable transportation. The role of air transportation, especially commercial aviation, is very important in economic and social development as shown by the increase in demand for aviation services as measured by the growth of air passengers. Airports are an important means of transportation in the transportation sector. Cut Nyak Dhien Nagan Raya Airport has many facilities that support the flight implementation process and also improve services to air transportation service users, however, there is something that is an important concern, namely disruption or outages of the main electrical power source on the CCR with Type Cooper at Cut Nyak Dhien Airport. where when the main power source goes out, at Cut Nyak Dhien Airport the main electrical system at the airport will go out for eight seconds and this will disrupt flights, especially when the plane is about to take off or land, because the CCR is a vital part when there is a flight, so CCR cannot be contested. Due to the problem of damaged UPS (Uninterruptible Power Supply) in the CCR Room at Cut Nyak Dhien Nagan Raya Airport, it will not operate properly and smoothly when there is a problem with the electricity in the airport CCR room, because the UPS is very influential for the smooth running and security of Cut Nyak Dhien airport. The function of the UPS is to supply electrical power requirements to the load. Quality and balanced electrical power is a priority in the world of aviation. Even the slightest electrical disturbance will disrupt the flight process chain and this can result in financial losses